PENGARUH LATIHAN SENAM AEROBIK KRONIK TERHADAP MEMORI JANGKA PENDEK SISWA SMP NEGERI 2 KUPANG - Bulu, Rosalina Steny; Kareri, Dyah G. Rambu; Sasputra, I Nyoman; Wungouw, Herman Pieter L. (Cendana Medical Journal, 2022)
Background Short term memory is an active memory storage capacity which actively saving information in a limit capacitry and has important role of mental consciousness. Memory describe the capacity of learning and it has strong relation of hippocampus role. Aerobic exercise is a kind of activity which can stimulates children’s cognition. Objective Prove an Chronic Aerobic Exercise on student’s short term memory. Method A study with Quasi experimental design has been made student of SMP Negeri 2 Kupang, the student are divided to 2 groups consist of 30 in control group and with the same amount un treated group than their short term memory fuction were taken and been measured. Result The results showed no change in test scores in the treatment group but only significant differences were found in the difference in scores on digit span and backward digit tests. Conclusion There was no chronic effect of aerobic exercise on short term memory in student at SMP Negeri 2 Kupang